2021
DOI: 10.3390/ijms22084130
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Atopic Dermatitis Pathogenesis

Abstract: Atopic dermatitis is a chronic, non-infectious inflammatory dermatosis. Acharacteristic feature is persistent itching of the skin. The chronic, relapsing course of the disease, economic burden, and the whole family’s involvement in the treatment process immensely reduce the quality of life of patients and their families. The disease emerges as a social problem by increasing indirect costs, such as visiting a doctor, absenteeism from work and school, and avoiding social interactions. Thepathophysiology of atopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
198
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(209 citation statements)
references
References 105 publications
1
198
0
10
Order By: Relevance
“…Phase II clinical trials with tezepelumab showed limited efficacy and statistically insignificant clinical improvement. Further studies may be required with longer treatment periods for better treatment effects [191][192][193][194].…”
Section: Emerging Therapeutic Biologics For Admentioning
confidence: 99%
“…Phase II clinical trials with tezepelumab showed limited efficacy and statistically insignificant clinical improvement. Further studies may be required with longer treatment periods for better treatment effects [191][192][193][194].…”
Section: Emerging Therapeutic Biologics For Admentioning
confidence: 99%
“…Патофизиология АтД многогранна и включает в себя сложное взаимодействие таких факторов, как дисфункция эпидермального барьера и дисрегуляция иммунного ответа, происходящее на фоне наследственной предрасположенности и действия на организм неблагоприятных условий внешней среды [1,8]. Одним из основных компонентов эпидермального барьера является роговой слой, формирующийся за счет процессов дифференцировки и ороговения кератиноцитов, в ходе которых синтезируется ряд важных структурных белков (в частности, филаггрин, лорикрин, инволюкрин), участвующих в реализации барьерной функции кожи [9,10]. Соответственно изменения нуклеотидной последовательности генов структурных белков приводят к дефектам эпидермального барьера, ведущим к повышению уровня pH и трансэпидермальной потери воды с последующим развитием ксероза, а также к нарушению пропорций и количества свободных жирных кислот, церамидов и триглицеридов кожи [9,11].…”
Section: патофизиология атопического дерматитаunclassified
“…Мутации генов структурных белков, белков межклеточных соединений или протеаз, помимо дисфункции эпидермального барьера, влекут за собой активацию иммунного ответа из-за деградации межклеточных связей, увеличения активности протеаз и, как следствие, повышения проницаемости эпидермиса для антигенов внешней среды (микроорганизмы, аллергены) [10]. Нарушение регуляции иммунного ответа в острой фазе АтД обусловлено преимущественно дифференцировкой наивных Т-лимфоцитов в Th 2 -и Th 22 -клетки, вырабатывающие значимые для патогенеза АтД провоспалительные интерлейкины (IL-4, -5, -13, -22 и -31) [8], а также формированием IgE-опосредованной гиперчувствительности [14].…”
Section: патофизиология атопического дерматитаunclassified
“…Epigenome differences between AD patients and healthy people have been reported ( Mu and Zhang, 2020 ). In AD, epigenetic modifications target genes involved in immune regulation, genes of innate immunity, and genes encoding epidermal structural proteins ( Sroka-Tomaszewska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%